Interspeech 2016 2016
DOI: 10.21437/interspeech.2016-49
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Phonatory Behavior of German and French Speakers in Native and Non-Native Speech

Abstract: Phonatory behavior of German speakers (GS) and French speakers (FS) in native (L1) and non-native (L2) speech was instrumentally examined. Vowel productions of the two groups were analyzed using a parametrization of phonatory behavior and phonatory quality properties in the acoustic signal. The behavior of GS is characterized by more strained adduction of the vocal folds whereas FS show more incomplete glottal closure. Furthermore, GS change their phonatory behavior in the foreign language (=French) by adaptin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
1
0
0
Order By: Relevance
“…As in other studies on voice attractiveness the voice quality can play an important role [6]. In an investigation of the laryngeal phonatory settings of the corpus data also used in this study [18] it could be shown that the behaviour of German speakers is characterised by more strained adduction of the vocal folds whereas French speakers show more incomplete glottal closure.…”
Section: Discussionsupporting
confidence: 62%
“…As in other studies on voice attractiveness the voice quality can play an important role [6]. In an investigation of the laryngeal phonatory settings of the corpus data also used in this study [18] it could be shown that the behaviour of German speakers is characterised by more strained adduction of the vocal folds whereas French speakers show more incomplete glottal closure.…”
Section: Discussionsupporting
confidence: 62%